Improving the skills of demand function counting and demand curve drawing with the drill method and think pair share (tps) at the 1st year of social science students in state senior high school 11 semarang - Mulyani, Semi; Sofiani, Ani (Dinamika Pendidikan, 2016)
Based on the result of initial observation, it showed that studentâ knowledge and skills on counting and drawing activities at the evaluation of economic pre-cycle in 2016/2017 for class X IPS 4, were only 39% and 76%. The objective of this study was to determine whether there was an increase of demand function counting and demand curve drawing with the drill method. It was a classroom action research with the use of drill and think pair and share learning methods. The subjects of the research were students at class X IPS 4 in SMAN 11 Semarang. The data were analyzed by the simple descriptive statistics analysis with the mean of the evaluation result. The result of the study showed that drill and think pair share learning methods in Class X IPS 4 SMA Negeri 11 Semarang got the mean was 72.94 and 76.10 at the pre-cycle, with the study completeness was only 13 students (39%). After conducting the first cycle, there was an improvement for 78.06 and 89.04 with study completeness was 18 students (55%). And in the second cycle, studentsâ learning outcomes increased up to 95.76 and 99.29 with learning completeness was 33 students (100%).